Hubungan Likuiditas, Profitabilitas, Leverage Dan Earning Per Share Terhadap Underpricing pada Perusahaan Yang Melakukan Initial Public Offering (IPO) Tahun 2009-2018 - Nadya Khaira; Josephine Sudiman (The Indonesia Capital Market Institute, 2019)
This research aims to determine the relationship of liquidity, profitability, leverage and earnings per share on underpricing of companies conducting Initial Public Offering (IPO) from 2009 to 2018, using a purposive sampling method with a total sample of 156 companies. Secondary data obtained from the prospectus and the company's financial statements and Spearman rank-order correlation used for hypothesis testing. The results of this study indicate that: (1) Liquidity have no relationship with underpricing, (2) Profitability have a low relationship with underpricing, (3) Leverage has a very low relationship to underpricing, (5) Earning per share (EPS) variable has no relationship to underpricing.